The Changing River Thames: Some Thoughts from an Archaeological Perspective. (November 2015) - Milne, Gustav
Abstract : This article provides a brief introduction to the recent contribution of archaeology and geoarchaeology to understanding environmental change on the River Thames. Investigations following the 1953 East Coast flood and greater waterfront accessibility arising from the closure of the docks-assisted archaeological identification of a long-term upward trend in river levels, resulting from complex natural factors and centuries of human intervention. Archaeology has also benefited from greater exposure of the foreshore, but data collected by the Thames Discovery Programme and its predecessor has shown erosion and tidal scour to be increasing, with risks to waterfront structures. Whether this is a natural development or associated with new types of passenger vessel on the river is at present uncertain.